Sums of four or fewer squares - Aashita Kesarwani; V. H. Moll (Scientia Series A: Mathematical Sciences, 2025)
A classical theorem of Lagrange states that every positive integer is the sum of four squares. Properties of the sets obtained by fixing three, two or one of these squares are discussed.
Keywords: Squares; Lagrange theorem; representations by squares